POSSESSION, REVIEW FROM CULTURAL AND PSYCHIATRY - Sri Diniari, Ni Ketut; Hanati, Nyoman (Medicina, 2013)
Possession is a culture related syndrome, commonly found in Indonesia including Bali. We can see this event in religion and cultural ceremony and at other times at school, home, and in society. This syndrome consist of temporary loss of self identification and environment awareness; in several events a person acts as if he/she was controlled by other being, magic force, spirit or ‘other forces’. There are still several different opinions about trance-possession, whether it is related to certain culture or is a part of mental disorder. DSM-IV-TR and PPDGJ-III defined trance-possession as mental disorder (dissociative) for involuntary possession, if it is not a common activity, and if it is not a part of religion or cultural event. (MEDICINA 2012;43:37-40).
Keywords: possession, culture, psychiatry